ULTRASOUND DIAGNOSIS OF ADVENTITIAL BURSITIS AT THE FIRST METATARSAL HEAD - Soemarjono, Arif; Soewito, Ferius (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Adventitial bursitis in the plantar aspect of the first metatarsal heads is characterized by abrupt onset of localized deep and discomfort in the plantar aspect of the first metatarsal head aggravated by walking. Diagnosis of adventitial bursitis is difficult to be established based solely on clinical findings, conventional radiography does not allow diagnosis of soft-tissue disorders especially bursitis. Musculoskeletal ultrasound is a useful imaging modalities to support the clinical diagnosis of soft tissue disorders such as bursitis. To our knowledge, sonographic findings of adventitial bursitis have been rarely reported. Here we present a case report of a patient with pain in the plantar aspect of the left first metatarsal head.